Thermal environment as a management tool in high-rise building - Hélio Neto (2013)
The construction industry is a growing sector in countries that are prosperous in economic development, leading to the new studies that drive this sector. Thus, it appears that the buildings have a great relationship with thermal environment, due to their constant exposure to those factors. This can influence the productivity of workers, compromising the execution of construction. This paper aims at investigating the influence of the thermal environment in building at elevated heights, establishing a relationship with productivity. For that, was done a sistematic bibliographic research in this area trying to stablish the stat of the art starting from the papers published in the last ten years. It appears that there is a relationship between the subjects studied, although most of the survey does not include all the issues.